Rare case of Mycobacterium nebraskense presenting as asymptomatic cavitary lung lesion - Omar Abdulfattah; Antony Lixon; Saroj Kandel; Ebad Ur Rahman; Sasmit Roy; Sumit Dahal; Zainab Alnafoosi; Frances Schmidt (Journal of Community Hospital Internal Medicine Perspectives, 2018)
Introduction: Mycobacterium Nebraskense is a rare nontuberculous mycobacterial infection. The first isolate of the species was from human sputum at University of Nebraska Medical Center. There are only a few cases have been reported and the exact behavior of the disease is not clearly described. Here, we present a case from New York City incidentally found to have a cavitary lung lesion due to M. nebraskense. Case report: An 82-year-old female with a history of diabetes mellitus, hypertension, and dementia presented with constipation and urinary retention for 1 day. She had no fever, cough, shortness of breath, nausea, vomiting, appetite change, or weight loss. Computed tomography (CT) scan of abdomen and pelvis revealed retained fecal material in the colon, non-obstructing left renal calculus, and bilateral small pleural effusion with right-sided lung infiltrates. Subsequent CT scan of the chest showed 4.5 cm pleural-based opacity in right lung base with a small cavity. Sputum smear for Acid-fast bacilli was positive. Mycobacterial culture reported positive growth of M. nebraskense, while polymerase chain reaction returned negative for Mycobacterium gordonae, Mycobacterium kansasii, Mycobacterium avium complex and Mycobacterium tuberculosis. With the patient asymptomatic and her constipation improved, she was discharged with plans for close follow-up as outpatient. Conclusion: M. nebraskense is a very rare nontuberculous mycobacterial infection. From only a few cases reported in the USA, the exact presentation of infection, disease progression, and treatment have not been described well. Asymptomatic cavitary lung disease caused by M. nebraskense has not been reported before.